Principles of Caution by Notaries Regarding Transfer of Land Rights Based on A Name-Border Agreement from the Perspective of Land Registration Regulations - Artamira, Nabela Maulinda; Handayani, Sri Wahyu (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
not recognized by the Civil Code but grow and develop in society. This practice has become a fairly common phenomenon, especially in regional areas. a popular tourist area, where many foreigners are interested in owning property but are prevented by applicable legal provisions. Agrarian law strictly prohibits foreigners from owning land with freehold rights. This not only has the potential to harm the country financially, but also creates legal uncertainty that can hamper the long-term investment climate. From a public policy perspective, the existence of name loan agreements reflects a gap between market needs and the existing legal framework. A comprehensive study is needed to formulate policies that can accommodate global economic dynamics without compromising the fundamental principles of national agrarian law. The research method used is normative juridical, the type of approach used is a conceptual approach and a legislative approach, the data analysis method used is a literature study using qualitative analysis. The results of this study are that the position of the nominee agreement also has the potential to cause legal uncertainty and social conflict, especially if there are dual claims to land ownership, in practice, the court tends to reject the Nominee agreement because it violates the principle of nationality which is the main basis of the Basic Agrarian Law. The principle of caution has an important role for Notaries in carrying out their duties and authorities, so that Notaries must play a role in providing legal counseling to the parties regarding the contents that will be stated in the form of a Deed so that in the implementation of the principle of accuracy or caution must be carried out in the process of making a deed.